Perspektif Hukum terhadap Tindak Pidana Online Fraud dalam E-Commerce: Peran Kebijakan Internasional - Rachman, Rahmia; Silalahi, Elyezer Hamonangan; Dahlan, Intje Safira (Fakultas Hukum Universitas Islam Malang, 2025)
Online fraud crime causes various losses to business actors and consumers. This has an impact on the decline in consumer confidence in e-commerce platforms. This research aims to analyze legal protection and the role of international policies on consumer protection in e-commerce. This research uses normative juridical method. Legal protection is provided preventive efforts, namely providing socialization about fraud modes and platform security systems, as well as repressive efforts through law enforcement (Article 28 paragraph (1) of the ITE Law, Article 378 of the Criminal Code and Article 62 of the GCPL), strengthening e-commerce consumer protection. The role of e-commerce platforms in preventing online fraud is very important, as they provide a secure payment system, verify sellers and authenticity of goods, monitor suspicious transactions, and ensure clear buyer protection. Cooperation with authorities and consumer education is also important to create a safe and trusted digital environment.